مؤسسات المجتمع المدني وثقافة المواطنة - دلهوم, مفيدة (جامعة الوادي - University of Eloued, 2018)
في ظل التطورات التكنولوجية والتحولات الثقافية والاجتماعية والسياسية والاقتصادية التي يشهدها العالم، لا تستطيع الدولة وحدها تلبية كافة احتياجات افرادها ،ومع ظهور مفاهيم جديدة تتعلق بحقوق الإنسان والمشاركة المجتمعية ، كان ضروريا مساعدة هذه المؤسسات للدولة وهذا للوصول إلى مجتمع ديمقراطي واعي بحقوقه وواجباته وذلك بتعزيز قيم الانتماء ثقافة المواطنة وما يترتب عنها من قيم المشاركة والانتماء.In the light of the technological developments and cultural, social, political and economic changes taking place in the world, The state alone can not meet all the needs of its members, and with the emergence of new concepts related to human rights and community participation, it was necessary to help these institutions to the state and this to reach a democratic society conscious of its rights and duties by promoting the values of belonging Culture of citizenship and the consequent values of participation and belonging.
مقال
Keywords: المواطنة ، مؤسسات المجتمع المدني، الديمقراطية ، حقوق الانسان .; citizenship - civil society institutions links, democracy, human Rights